Decisions made on the Development of the Hill Station of Cameron Highlands from 1884 till present day - Weebers, Robert C.M.; Idris, Hanizah (Journal of Surveying, Construction and Property, 2016)
The aim of this paper is to show which decisions were taken to direct the development of Cameron Highlands with regard to the usage of the area from 1884 till the present day. Is the character of Cameron Highlands maintained as a hill station for relaxation and health as intended by the British or does the development take another direction. The development of Cameron Highlands is well planned and organized by the British. The hill station is meant to be a sanatorium, for relaxation, amusement and agriculture (tea plantations and vegetable farms). Decisions are made on the construction of roads, the lay-out of the area, distribution of land for residential or agricultural use, on the establishment of townships and the erection of buildings. Present day development of Cameron Highlands is linked to tourism (agro-tourism, eco-tourism and cultural and heritage tourism). In the last years a dramatic increase in the development in Cameron Highlands takes place where areas of forests are cleared for vegetable and flower growing as well as for housing development. This has resulted in soil erosion problems, siltation of lakes and rivers. There is an urgent need for conservation, agriculture, watershed protection and resort development.